2021
DOI: 10.1002/ptr.7303
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of fucoidan on breast cancer cells and potential enhancement of their sensitivity to chemotherapy by regulating autophagy

Abstract: Fucoidan is a marine‐origin sulfated polysaccharide that has gained attention for its anticancer activities. However, the inhibitory effect of fucoidan on breast cancers by regulating autophagy and its mechanism are not clear, and the chemotherapeutic sensitization of fucoidan is largely unknown. In the present study, the anticancer potential of fucoidan was revealed in MCF‐7 and MDA‐MB‐231 cells. Additionally, we also studied the chemotherapeutic sensitization of fucoidan by combining chemotherapeutic drugs d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 54 publications
(65 reference statements)
0
12
0
Order By: Relevance
“…It was applied to combined treatments with several anticancer drugs. Taking the example of breast cancer cells, FN combined with cisplatin, tamoxifen, paclitaxel [ 38 ], and doxorubicin [ 23 ] exhibit synergistic antiproliferation effects. Combined treatment of FN with tyrosine kinase inhibitor lapatinib suppresses more proliferation of esophageal cancer cells (OE33) [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was applied to combined treatments with several anticancer drugs. Taking the example of breast cancer cells, FN combined with cisplatin, tamoxifen, paclitaxel [ 38 ], and doxorubicin [ 23 ] exhibit synergistic antiproliferation effects. Combined treatment of FN with tyrosine kinase inhibitor lapatinib suppresses more proliferation of esophageal cancer cells (OE33) [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the combined treatment of anticancer agents with FN was reported using cisplatin [ 23 ], gefitinib [ 24 ], and vitamin C [ 25 ] for lung, breast, and colon cancer cells, respectively, while the combined treatment of anticancer therapy with FN in oral cancer was rarely applied, particularly together with UVC irradiation.…”
Section: Introductionmentioning
confidence: 99%
“…Previous experiments have focused on combining fucoidan in a therapeutic system to obtain gatekeeper [ 50 ], target molecule [ 51 ], and anticancer drug [ 52 ] functions, but only for one or two fucoidan functions. In this experiment, we are the first person to integrate all fucoidan functions into one therapeutic system but are still affected by the instability of algal extracts.…”
Section: Discussionmentioning
confidence: 99%
“…Zhang et al found that fucoidan induced autophagy in breast cancer cells by down-regulating mTOR/p70S6K/TFEB pathway, thus inhibiting tumor development. At the same time, they also explored the chemotherapeutic sensitization of fucoidan and concluded that fucoidan might enhance the sensitivity of breast cancer cells to chemotherapeutic drugs doxorubicin and cisplatin [125]. These findings will help researchers to further explore the regulatory role of TFEB in cancers as one of the effective targets for anticancer therapy.…”
Section: Promotion Of Autophagy In Anticancer Therapymentioning
confidence: 95%